A conceptual model of interactive persuasive learning system for elderly to encourage computer-based learning process - Zulkifli, Abdul Nasir; Mohamed Noor, Nurtihah; Abu Bakar, Juliana Aida; Che Mat, Ruzinoor; Ahmad, Mazida (2013)
Over the past few years, new and improved learning techniques and technologies have been introduced.Among them, interactive media holds a lot of potential in learning.This technology highly promotes self-directed and active learning approaches and has capabilities to foster the learning process. Furthermore, the emergence of persuasive technology increased the capability of the media features to be used in learning field within variety of ways. Persuasive technology is the attempts of several researchers and its founder to proof the power of persuasion through the computer technology in changing peoples’ behavior and attitude.Even though previous studies have highlighted the various features of interactive media contribute to learning, our preliminary study indicated that most of elderly prefers conventional learning approach over computer approach.It is evident that elderly choose the use of computer applications as their last resort in learning.In order to highlight an interactive media system with persuasion elements, this study attempt to propose a conceptual model of interactive persuasive learning system for elderly that can be used in encouraging them to learn using computer-based learning tools. Thus this paper reviews the introduction of persuasive technology and interactive media. Then, we propose the conceptual model of interactive persuasive learning system for elderly that can be used in encouraging them to learn using computer-based learning tools. The proposed model will be helpful in designing and developing interactive media systems that can encourage and engage a learning process among elderly.